2001
DOI: 10.1002/1099-0488(20010215)39:4<432::aid-polb1015>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Total-reflection X-ray diffraction study of friction-transferred poly(tetrafluoroethylene) film

Abstract: The orientational structure of the friction‐transferred poly(tetrafluoroethylene) (PTFE) film, which consists of highly oriented polymer strands, was evaluated with energy‐dispersive total‐reflection X‐ray diffractometry. In the film, each PTFE molecule is oriented along the friction direction, and PTFE crystallites have a preferred orientation with respect to the substrate surface. The orientational distribution of the chain direction was quantitatively evaluated. The half‐width of the distribution was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Moreover, since the thin film of PTFE is formed only in the confined area which drew a PTFE block by friction-transfer technique, it is possible be easily pattern a polymer film by a drawing method. In addition, from the results of transmission electron microscopy ͑TEM͒ 6 and x-ray diffraction ͑XRD͒ analysis, 7 it was confirmed that the friction-transferred PTFE film was having highly oriented polymer backbones along the drawing direction. The friction-transfer technique can form polymer aligned film without any underlying alignment layer.…”
mentioning
confidence: 91%
“…Moreover, since the thin film of PTFE is formed only in the confined area which drew a PTFE block by friction-transfer technique, it is possible be easily pattern a polymer film by a drawing method. In addition, from the results of transmission electron microscopy ͑TEM͒ 6 and x-ray diffraction ͑XRD͒ analysis, 7 it was confirmed that the friction-transferred PTFE film was having highly oriented polymer backbones along the drawing direction. The friction-transfer technique can form polymer aligned film without any underlying alignment layer.…”
mentioning
confidence: 91%
“…These results suggest that the a and b axes have some orientation concerning the substrate plane. We have observed preferential orientations concerning the substrate in the friction-transferred films of P3ATs [ 40 , 41 ]. Now, we suppose PT molecules take a preferential arrangement in which the a -axis is normal to the substrate, the b -axis is in the substrate plane, and the molecular chains ( c -axis) are in the substrate plane and aligned along the friction transfer direction, as shown in Figure 7 , because of the following reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in order to evaluate the orientation of the crystallites regarding the substrate plane, energy-dispersive (ED) GIXD measurements [ 39 , 40 , 41 ] were carried out. The schematic diagram of ED-GIXD geometry is illustrated in Figure 1 b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy‐dispersive (ED) GIXD measurements were performed to evaluate the orientation of the crystallites of RR‐P3DDT in the films. The details of the experimental setting were as described previously . The ED‐GIXD system was constructed by Rigaku.…”
Section: Methodsmentioning
confidence: 99%